Inability of Protecting Diplomats: Problems of Afghanistan and Conflict Countries - Ananda Kurniawan Sukarmaji; Arie Afriansyah (Sriwijaya Law Review, 2018)
This article discusses the protection of diplomats and state responsibility of physical suffering of diplomats in conflict countries, especially in Afghanistan using juridical normative methodology. This concern has to be discussed because there are a lot of attacks and physical harms suffered by the diplomats, especially in armed-conflict countries. This article analyzes the practices of protection of diplomats in some conflict countries and explain the conventions that include protection of diplomats as a part of the conventions. Thus, conflict countries are more tendentious than non-conflict countries in terms of numbers of attacks and physical harms suf-fered by diplomats. Therefore, this article analyzes the conflict country and categorizes the terms and conditions in the conflict countries. After looking into the pattern of protection of dip-lomats in some countries, this article analyzes the response shown by the receiving and sending state. There is also a discussion of the attacked diplomat cases in Afghanistan and the responses issued by the related parties. Then, protection of the diplomats and state responsibility are ana-lyzed based on the related doctrine and conventions. Changes in protection of diplomats in Af-ghanistan should be done and Afghanistan should be more concerned about this matter and based on the diplomatic convention, sending state could file a dispute settlement to an arbitrary organ and International Court of Justice to claim state responsibility. Based on the conventions and doctrine related, Afghanistan could be charged as the full responsible party